Learning the Right Skill: The Returns to Social, Technical and Basic Skills for Middle-Educated Graduates - Femke Cnossen; Matloob Piracha; Guy Tchuente (Global Labor Organization (GLO), 2021)
Technological change and globalization have sparked debates on the changing demand for skills in western labour markets, especially for middle skilled workers who have seen their tasks replaced. This paper provides a new data set, which is based on text data from curricula of the entire Dutch vocational education system. We extract verbs and nouns to measure social, technical and basic skills in a novel way. This method allows us to uncover the skills middle-skilled students learn in school. Using this data, we show that skill returns vary across students specialized in STEM, economics or health, as well as across sectors of employment.
Keywords: J24; I26; I21; 330; Curriculum skills; vocational education and training; skill returns